Perancangan Game Edukasi Pramuka 2D Berbasis Android (Studi Kasus SDS Adhyaksa 1 Kota Jambi - Gilang Prakoso, Amandha; Irawan; Sukoco, FA Bambang (Jurnal Manajemen Teknologi Dan Sistem Informasi (JMS), 2024)
The Scout Movement originated from the concept of Sir Robert Baden-Powell and was introduced in Indonesia in 1912. This movement aims to develop the physical, mental, emotional, and spiritual aspects of its members. The Indonesian government has mandated scouting as a compulsory extracurricular activity in middle schools. SDS Adhyaksa 1 in Kota Jambi implements scouting as a compulsory extracurricular but faces challenges in its teaching.To address this, the proposal suggests creating a scouting educational game based on Android. This game is expected to enhance students' interest and understanding of scouting materials. The waterfall system development model is utilized in designing this application, encompassing analysis, design, coding, testing, and supporting stages.The research outcome introduces an alternative scouting learning method through an interactive Android-based educational game. The hope is that this innovation can serve as a solution to enhance the quality of scouting education at SDS Adhyaksa 1 and other schools.